What Is Common Among Return Anomalies? Evidence from Insider Trading. Issue 3 (2nd July 2016) - Goukasian, Levon; Ma, Qingzhong; Zhang, Wei
ABSTRACT: For a broad set of anomalies, we establish a common pattern of underreaction to information contained in preceding insider trading activity. Our main analysis focuses on the anomalies' short legs, which generate persistent negative abnormal returns. For stocks in the short legs, future returns are systematically related to the information signal contained in preceding insider trading activity, indicating underreaction. For insider trading information, we consider the possibility of net buying, net selling, and no trading (or silence). The underreaction effect is economically significant, with the most negative signal accounting for an average of 71% of short-leg returns. This underreaction effect survives numerous robustness checks and remains important after accounting for investor sentiment, information environment, and limits to arbitrage.